Effect of Green Logistics on Sustainability Performance in Malaysia Manufacturing Companies - Ashfaq, Muhammad; Qureshi, Imran; Irum, Sobia; Mehmood, Nasir; Khan, Nohman; Ahmad, Humara (International Journal of Psychosocial Rehabilitation, 2020)
Globalization and economic growth the world over resulted in the massive consumption of goods. Environmental challenges have also been evolved as a result of transportation, storage, production and consumption of these goods. This paper presents the contribution of operations research in the green logistics, which encompasses integrating environmental aspects in logistics. This paper provides present and potential developments in green logistics. The survey respondents were taken from the “Federation of Malaysian Manufacturers (FMM) directory of Malaysian Manufacturers 2017”. This directory contains information of manufacturing companies (large and small) from various sectors. The population of this study consists of all medium and large manufacturing companies of Malaysia with a total of more than 35000. The number of acceptable respondents for the present study is based on krejcie and Morgan table and according to that table the sample size for this study will be 346. For this study the statistical tool used will be Smart- PLS. To achieve this study’s objectives, a questionnaire was developed for measuring this study’s constructs of GL practices, environmental collaboration and sustainability performance. PLS_SEM was used for data analysis and hypothesis testing by exploring the relationships between independent and dependent variables simultaneously. The two-fold aim of this paper is: (i) review of existing literature on the relationship between GL, environmental collaboration and sustainability performance and (ii) proposing and testing a conceptual model to find the relationship between these variables in the context of Malaysian manufacturing companies. The research findings will be particularly important for manufacturing companies in developing environmental collaboration with their suppliers in order to achieve sustainability performance.